FINTECH, SDG PERFORMANCE, AND FIRM VALUE: THE MODERATING ROLE OF BANKING CORPORATE GOVERNANCE - Rida Izmaliani; Anik Puji Handayani; Gigih Aulia Hilmiawan (Universitas Riau, 2026)
The inconsistent empirical relationship between Financial Technology (FinTech), Sustainable Development Goals (SDGs), and firm value in emerging markets reveals a critical research gap regarding how market skepticism toward sustainability costs is managed. This study evaluates the impact of FinTech, SDG 8, and SDG 9 on firm value, with Good Corporate Governance (GCG) as a moderator. Analyzing 185 observations from 37 conventional banks on the Indonesia Stock Exchange (2020-2024), the research employs Moderated Regression Analysis (MRA) with a Fixed Effect Model. The findings indicate that only SDG 8 has a significant positive effect on firm value, confirming the existence of an ESG premium in the Indonesian market. Conversely, FinTech and SDG 9 do not exert a direct influence, reflecting investor preference for short-term profitability over capital-intensive infrastructure expenditures. Crucially, the results prove that GCG significantly strengthens the influence of FinTech on firm value, acting as a signal validator that validates the credibility of digital investments and mitigates agency concerns. However, GCG fails to moderate the SDG relationship due to structural barriers of investor short-termism. This study integrates Signaling and Agency theories, identifying GCG as a critical signal validator that converts technological investment costs into market-perceived firm value